Uptake and bioconversion of stereoisomeric dipeptide prodrugs of ganciclovir by nanoparticulate carriers in corneal epithelial cells. (1st September 2016) - Yang, Xiaoyan; Sheng, Ye; Ray, Animikh; Shah, Sujay J.; Trinh, Hoang M.; Pal, Dhananjay; Mitra, Ashim K.
Abstract: Purpose : The objective of this study is to investigate cellular uptake of prodrug-loaded nanoparticle (NP). Another objective is to study bioconversion of stereoisomeric dipeptide prodrugs of ganciclovir (GCV) including L-Val-L-Val-GCV (LLGCV), L-Val-D-Val-GCV (LDGCV) and d -Val-l -Val-GCV (DLGCV) in human corneal epithelial cell (HCEC) model. Methods : Poly(D, L -lactic- co -glycolic acid) (PLGA) NP encapsulating prodrugs of GCV were formulated under a double emulsion method. Fluorescein isothiocyanate isomer–PLGA conjugates were synthesized to fabricate biocompatible fluorescent PLGA NP. Intracellular uptake of FITC-labeled NP was visualized by a fluorescent microscope in HCEC cells. Results : Fluorescent PLGA NP and non-fluorescent NP display similar hydrodynamic diameter in the range of 115–145 nm with a narrow particle size distribution and zeta potentials around −13 mV. Both NP types showed identical intracellular accumulation in HCEC cells. Maximum uptake (around 60%) was noted at 3 h for NP. Cellular uptake and intracellular accumulation of prodrugs are significantly different among three stereoisomeric dipeptide prodrugs. The microscopic images show that NPs are avidly internalized by HCEC cells and distributed throughout the cytoplasm instead of being localized on the cell surface. Following cellular uptake, prodrugs released from NP gradually bioreversed into parent drug GCV. LLGCV showed the highest degradation rate, followed by LDGCV and DLGCV. Conclusion : LLGCV, LDGCV and DLGCV released from NP exhibited superior uptake and bioreversion in corneal cells.